2001
DOI: 10.1002/ar.1075
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the obturator internus, gemelli and quadratus femoris muscles with special reference to their innervation

Abstract: The manner of innervation of the obturator internus, superior and inferior gemelli, and the quadratus femoris in humans (101 pelvic halves) and in rhesus monkeys (Macaca mulatta: 8 pelvic halves) were investigated. In most specimens, the inferior gemellus originated from the lateral surface of the ischial tuberosity and also from the medial surface (intrapelvic origin) just beneath the obturator internus and was covered by the falciform process of the sacrotuberous ligament. The superior gemellus was frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 11 publications
3
45
1
Order By: Relevance
“…11 The OI possesses unique anatomy among the hip short external rotators. 12 It originates from within the pelvis along the obturator foramen and membrane, exits through the lesser sciatic foramen by curving around the posterior ischium, and courses laterally deep to the sciatic nerve toward its common insertion with the gemelli on the medial side of the greater trochanter. 13 Similar to the piriformis, the OI functions primarily as a hip external rotator and may assist in abducting the flexed hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The OI possesses unique anatomy among the hip short external rotators. 12 It originates from within the pelvis along the obturator foramen and membrane, exits through the lesser sciatic foramen by curving around the posterior ischium, and courses laterally deep to the sciatic nerve toward its common insertion with the gemelli on the medial side of the greater trochanter. 13 Similar to the piriformis, the OI functions primarily as a hip external rotator and may assist in abducting the flexed hip.…”
Section: Discussionmentioning
confidence: 99%
“…We performed B-mode, real-time ultrasonography using the ACCUVIX A30 system (Samsung, Seoul, South Korea) interfaced with a linear array transducer (5)(6)(7)(8)(9)(10)(11)(12). An investigator (S.C.L.)…”
Section: Methodsmentioning
confidence: 99%
“…Bardeen (1906) proposed that the obturator internus and gemelli muscles derive from a common outline, and then the obturator internus muscle moves toward the intrapelvic space to cover the obturator foramen. Aung et al (2001) indicated that during migration, the muscle bundles that extend medially to the ischiopubic ramus form the obturator internus muscle, and those which remain lateral to the ramus, form the gemelli muscles.…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a hip external rotator and assists adduction [3,4]. The quadratus femoris muscle is innervated by the quadratus femoris nerve which rises from the ventral roots of the L4, L5 and S1 nerves in 79.4% of patients [5]. In adults, the myotendinous junction is the most vulnerable location for injury [6,7].…”
Section: Discussionmentioning
confidence: 99%